Injury as a stressor in 67 first year contemporary dance students: a longitudinal cohort study - Kaufmann, Judith-Elisa; Stubbe, Janine H.; van Rijn, Rogier M.; Nelissen, Rob G. H. H.; Gademan, Maaike G. J. (Frontiers in Psychology, 2025)
IntroductionIn athletes, injuries lead to increased stress but athletes cope better with subsequent than with first-time-injury. In dancers such information is lacking. Thus, we investigated whether injuries are associated with increased stress-levels, and if subsequent injuries are associated with higher perceived stress levels than first injury.MethodsBachelor dance students were prospectively followed during five academic years (2016-2022). During the first month of the year, respectively, baseline characteristics were recorded using the “Performing artist and Athlete Health Monitor” (PAHM) including the VAS pain scale, the VAS stress scale, and the “Oslo Sport Trauma Research Centre Questionnaire on Health Problems” (OSTRC). Throughout the year, stress, injuries and injury severity were reported monthly. The first-month assessment served as baseline in which dancers had to be injury free to be included in this analysis. Paired t-tests were conducted.Results67 dancers (age 18.8 ±.8 years, 58.2% female) sustained at least one injury, of those 33 at least one subsequent injury. OSTRC severity scores ranged from a mean of 28.7 ±17.5 for first injuries to 31.4 ±17.1 for subsequent injuries. The mean baseline stress level for injuries was 24.3 ±17.2. Stress levels during first and subsequent injuries were elevated compared to the baseline stress levels, 34.8 ± 18.7 and 35.1 ±23.0, respectively. There were no differences between stress levels during first and subsequent injuries.DiscussionInjuries are associated with increased stress levels in dancers, but stress levels were equally high after first and subsequent injury. We emphasize the importance of a holistic approach to injury rehabilitation, thus not only focusing on the physiological injury as such, but also include the dancers’ psychological recovery and a focus on stress management for both enhanced recovery as well as prevention of future injuries.